Pengembangan Teknologi E-Government Organisasi Kemasyarakatan Kalimantan Tengah Pada Organisasi Pergerakan Mahasiswa Islam Indonesia (PMII) Berbasis Web - Siti Rahma Wita (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Social organization is an organization which is established and formed by the community voluntarily, their wants, needs, interests, activities and objectives to participate in development in order to achieve the objectives of the Republic of Indonesia. The selection of the right information system will help in the operational activities of companies, schools, community organizations and student organizations in Indonesia, one of which is student organizations namely the Indonesian Islamic Student Movement or abbreviated as PMII. PMII is a student organization that is outside the campus or referred to as an external campus organization. In this study will build an administrative management system in an organization.